Immune reactions after modern lamellar (DALK, DSAEK, DMEK) versus conventional penetrating corneal transplantation. (November 2019) - Hos, Deniz; Matthaei, Mario; Bock, Felix; Maruyama, Kazuichi; Notara, Maria; Clahsen, Thomas; Hou, Yanhong; Le, Viet Nhat Hung; Salabarria, Ann-Charlott; Horstmann, Jens; Bachmann, Bjoern O.; Cursiefen, Claus
Abstract: In the past decade, novel lamellar keratoplasty techniques such as Deep Anterior Lamellar Keratoplasty (DALK) for anterior keratoplasty and Descemet stripping automated endothelial keratoplasty (DSAEK)/Descemet membrane endothelial keratoplasty (DMEK) for posterior keratoplasty have been developed. DALK eliminates the possibility of endothelial allograft rejection, which is the main reason for graft failure after penetrating keratoplasty (PK). Compared to PK, the risk of endothelial graft rejection is significantly reduced after DSAEK/DMEK. Thus, with modern lamellar techniques, the clinical problem of endothelial graft rejection seems to be nearly solved in the low-risk situation. However, even with lamellar grafts there are epithelial, subepithelial and stromal immune reactions in DALK and endothelial immune reactions in DSAEK/DMEK, and not all keratoplasties can be performed in a lamellar fashion. Therefore, endothelial graft rejection in PK is still highly relevant, especially in the "high-risk" setting, where the cornea's (lymph)angiogenic and immune privilege is lost due to severe inflammation and pathological neovascularization. For these eyes, currently available treatment options are still unsatisfactory. In this review, we will describe currently used keratoplasty techniques, namely PK, DALK, DSAEK, and DMEK. We will summarize their indications, provide surgical descriptions, and comment on their complications and outcomes. Furthermore, we will give an overview on corneal transplant immunology. A specific focus will be placed on endothelial graft rejection and we will report on its incidence, clinical presentation, and current/future treatment and prevention options. Finally, we will speculate how the field of keratoplasty and prevention of corneal allograft rejection will develop in the future. Highlights: Novel lamellar keratoplasty techniques have revolutionized corneal transplant surgery and immunology. Lamellar keratoplasty significantly reduces the risk of endothelial graft rejection. After (high-risk) penetrating keratoplasty, graft rejection is still very relevant.